Disease progression and search for monogenic diabetes among children with new onset type 1 diabetes negative for ICA, GAD- and IA-2 Antibodies - Pörksen, Sven; Laborie, Lene Bjerke; Nielsen, Lotte; Louise Max Andersen, Marie; Sandal, Tone; de Wet, Heidi; Schwarcz, Erik; Aman, Jan; Swift, Peter; Kocova, Mirjana; Schönle, Eugen J; de Beaufort, Carine; et al. (BMC Part of Springer Nature, 2010)
To investigate disease progression the first 12 months after diagnosis in children with type 1 diabetes negative (AAB negative) for pancreatic autoantibodies [islet cell autoantibodies(ICA), glutamic acid decarboxylase antibodies (GADA) and insulinoma-associated antigen-2 antibodies (IA-2A)]. Furthermore the study aimed at determining whether mutations in KCNJ11, ABCC8, HNF1A, HNF4A or INS are common in AAB negative diabetes.